Resilience in female athletes: a meta-analysis of levels, gender differences, and associations across psychosocial, performance, and health domains - Xiangnan Li; Jiajie Pan; Rouhan Liu; Yao Chen; Xinxue Zhu; Yongqiang Su (Frontiers in Psychology, 2026)
Introduction Psychological resilience is considered a central component of athletes adaptability, competitive performance, and psychosocial functioning. However, the evidence regarding psychological resilience among female athletes remains fragmented, particularly with regard to its levels, gender differences, and associated psychological factors. Methods This meta-analysis followed the PRISMA guidelines and synthesized 76 studies involving 27,386 coded participants, including at least 14,804 female athletes and 9,719 male athletes with sex-specific sample sizes available. This study examined resilience-related levels among female athletes, gender differences, and female-specific associations across psychosocial, performance, and health-related domains. Results The results indicate that female athletes resilience-related scores were generally located above the theoretical midpoints of the measures used, although comparative studies showed that female athletes scores were slightly lower than those of male athletes. Formal moderator tests supported age stage, but not construct type, competitive level, sport type, or injury/adversity context, as a source of variation in female-male differences. Correlational analyses indicated that higher resilience-related capacities were associated with more favorable psychosocial indicators, better coping and adaptation, lower distress or risk indicators, and stronger performance- or fitness-related indicators. Discussion The findings suggest that resilience in female athletes is best understood as a situational resource for athletic performance and health, rather than an unconditional psychological advantage. These findings are consistent with relational and resource based models of resilience and suggest that future efforts to support female athletes should combine the development of psychological capacities with improvements in the supportive environments in which they train and compete.